GC-MS Profile of Antioxidant Secondary Metabolites of Red Ginger from Batu Malang with Hepatoprotector Effect on Wistar Rats Exposed to Ethanol - Linia Nitrika; Nanik Marfu'ati; Maya Dian Rakhmawatie (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2023)
The liver is the organ most susceptible to the adverse effects of alcohol use. Decreased superoxide dismutase can be used as an indicator of liver cell damage due to excessive alcohol consumption. Red ginger (Zingiber officinale var. Rubrum) is known to have a hepatoprotective effect through antioxidant and anti-inflammatory mechanisms. This study was to prove the effect of red ginger extract from Batu Malang, Indonesia to restore normal levels of superoxide dismutase in the liver of Wistar rats induced by ethanol. Gas Chromatography-Mass Spectroscopy (GC-MS) metabolite profiling analysis of the red ginger ethanol extract was also carried out to ensure the presence of antioxidant compounds. Male Wistar rats were divided into 5 groups with 6 rats each, including negative control (C-) which was only given standard feed, positive control (C+) which was only given 1.8 mL/200g body weight of 40% ethanol orally, and treatment group which were given 40% ethanol as much as 1.8 mL/200 g body weight and red ginger extract at a dose of 250 (T1), 500 (T2), and 750 (T3) mg/kg body weight. Liver organs were taken to examine superoxide dismutase levels after 14 days of treatment in all groups. This research shows that ethanol with a concentration of 40% can reduce superoxide dismutase levels in the liver of rats significantly (p<0.05). All treatment groups that were given red ginger extract had higher superoxide dismutase levels than the positive control (C+) group (p <0.05), but the optimal dose to increase superoxide dismutase levels in Wistar rats induced by oral administration of 40% ethanol is 250 mg/kg body weight. Based on the results of metabolite profiling using GC-MS, found three dominant compounds thought to act as antioxidants, including Zingiberene, Gingerol, and 6-shogaol. Furthermore, further research is needed to evaluate the safety of using red ginger extract.